High Temperature Oxidation of Indefinite Chill Roll Material Under Dry and Humid Atmospheres. Issue 3 (27th May 2015) - Hao, Liang; Jiang, Zhengyi; Chen, Zhixin; Wei, Dongbin; Cheng, Xiawei; Zhao, Jingwei; Luo, Ming; Ma, Li; Luo, Suzhen; Jiang, Laizhu
Abstract : In this paper, the isothermal oxidation of the indefinite chill (IC) roll is investigated by using a thermogravimetric analyzer (TGA) from 550 to 700 °C under dry and humid atmospheres. It is found that the oxidation kinetics follow a linear trend and the oxide scale consists of two layers after the oxidation in dry air but three layers in humid air above 600 °C. In dry air, the graphite is covered by the oxide scale above 650 °C. The water vapor accelerates the oxidation of the matrix and the graphite. The graphite is covered by the extension of the oxide scale above 600 °C in humid air. The as‐treated samples are examined with SEM and XRD, while the kinetics is based on TGA results. Abstract : The isothermal oxidation of the indefinite chill (IC) roll (shown in Figure 1) is investigated by using a thermogravimetric analyzer . Results show that the oxidation kinetics follow a linear trend, and the oxide scale consists of two layers after the oxidation in dry air but three layers in humid air above 600 °C. The water vapor accelerated the oxidation of the matrix and the graphite.